New biochemical markers in acute coronary syndromes. - Tousoulis, D; Kampoli, A; Stefanadi, E; Antoniades, C; Siasos, G; Papavassiliou, A; Stefanadis, C (2008)
This article comments on the role of the most important biochemical markers that are already applied in clinical practice or are still under research, in Acute Coronary Syndromes (ACS). Cardiac troponin (cTn) is established as the 'gold standard' in the diagnosis of ACS. C-reactive protein (CRP) and especially high-sensitivity CRP (hs-CRP) are considered to be the most useful inflammatory markers for clinical practice in the setting of acute coronary syndrome. Brain-type natriuretic peptide (BNP) and the amino terminal fragment of the prohormone BNP (NT-proBNP) appear to provide prognostic information in individuals admitted for acute coronary syndromes. Microalbuminuria in nondiabetics appears to be a signal from the kidney that the vasculature, particularly the endothelium, is not functioning properly. Increased plasma levels of cystatin C, neopterin, myeloperoxidase, and pregnancy associated protein are associated with adverse cardiovascular outcomes, cardiovascular and noncardiovascular death, and possibly cerebrovascular disease. Furthermore, recent evidence suggests that serum levels of CD40-CD40L pathway exert important roles in progression, and outcome of acute coronary syndrome. In the future further, studies are necessary to elucidate the exact role of the new biochemical markers in ACS.